2010
DOI: 10.1007/s10311-010-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-electrode process with high efficiency for degradation of 2,4-dichlorophenol

Abstract: 2,4-Dichlorophenol (2,4-DCP) from chemical industry wastewaters has caused serious environmental pollution. Removal of 2,4-DCP using either physicochemical or biological methods is not very efficient. In this paper, a combination of biological and electrochemical methods gave satisfactory results. By comparisons of the degradation of 2,4-DCP and the removal of chemical oxygen demand (COD) in electrochemical, biological and biofilm-electrode processes, it was found that the biofilmelectrode process possesses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The removal efficiency of the investigated processes was 100%, 42%, and 61%, respectively. This improvement and increase in removal efficiency were due to the electrostimulation of bacteria (Zhang et al, 2011).…”
Section: -7-the Effect Of Electric Currentmentioning
confidence: 94%
See 3 more Smart Citations
“…The removal efficiency of the investigated processes was 100%, 42%, and 61%, respectively. This improvement and increase in removal efficiency were due to the electrostimulation of bacteria (Zhang et al, 2011).…”
Section: -7-the Effect Of Electric Currentmentioning
confidence: 94%
“…All these oxidants are produced in situ and used immediately; they can also be harmful to the biofilm in higher concentrations (García-García et al, 2015). Zhang et al, (2011) studied BER, in which microorganisms specifically attach to the electrode as a biofilm and play a pivotal role in biodegradation. They reported that applying over-optimum currents causes separation and fall-off microorganisms from the electrode (Zhang et al, 2011).…”
Section: Effect Of Applied Currentmentioning
confidence: 99%
See 2 more Smart Citations
“…Electric current stimulation improved microbial metabolism and azo reductase activity. Concurrently, the surface of the GAC layer was charged by the current to become new GAC electrodes, which can produce anode reactions on the surface [23]. This greatly increased the specific area of the electrodes [24] so that the 3D-BERs still had good removal efficiencies at high X-3B influent concentrations.…”
Section: X-3b Removal Efficiencies At Different Influent Concentrationsmentioning
confidence: 99%